Relationship Between Recount Text Generic Structure Mastery And English Reading Comprehension - Rahma Ayu, Siti (Catholic University Musi Charitas, 2024)
This study aims to investigate the relationship between students' mastery of the generic structure of recount texts and their English reading comprehension. The background of this research lies in the crucial role that understanding text structures plays in enhancing reading skills. A quantitative research design was employed, involving a sample of high school students who were assessed through tests measuring their knowledge of recount text structures and their reading comprehension abilities. Data collection involved administering structured tests and analyzing the results using statistical methods to determine correlations between the variables. The findings reveal a significant positive relationship between students' mastery of recount text structures and their reading comprehension, suggesting that better understanding of text structure facilitates improved comprehension. The study concludes that teaching the generic structure of texts can be an effective strategy in improving students' reading comprehension skills. Based on these findings, it is recommended that educators integrate explicit instruction on text structures into the reading curriculum to enhance students' overall reading abilities.